2005
DOI: 10.1093/nar/gki733
|View full text |Cite
|
Sign up to set email alerts
|

Induction of transcription within chromosomal DNA loops flanked by MAR elements causes an association of loop DNA with the nuclear matrix

Abstract: The spatial organization of an ∼170 kb region of human chromosome 19, including CD22 and GPR40–GPR43 genes, was studied using in situ hybridization of a set of cosmid and PAC probes with nuclear halos prepared from proliferating and differentiated HL60 cells. The whole region under study was found to be looped out into the nuclear halo in proliferating cells. It is likely that the loop observed was attached to the nuclear matrix via MAR elements present at the flanks of the area under study. Upon dimethyl sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 32 publications
2
31
0
1
Order By: Relevance
“…This result is similar to that obtained previously in experiments with a human genomic domain containing actively transcribed genes [Iarovaia et al, 2005]. Also, according to the previous data, the same 250 Kb DNA fragment was partially looped out from the nuclear matrix in DT40 cells where the central area of this fragment (including the domain of alphaglobin genes) is either not transcribed at all or transcribed at a very low level.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This result is similar to that obtained previously in experiments with a human genomic domain containing actively transcribed genes [Iarovaia et al, 2005]. Also, according to the previous data, the same 250 Kb DNA fragment was partially looped out from the nuclear matrix in DT40 cells where the central area of this fragment (including the domain of alphaglobin genes) is either not transcribed at all or transcribed at a very low level.…”
Section: Discussionsupporting
confidence: 91%
“…This finding correlates well with previous observations demonstrating that active genes are associated with the nuclear matrix [Ciejek et al, 1983;Robinson et al, 1983]. In our recent study we have demonstrated that activation of transcription of several tissue-specific genes within a large DNA loop domain induces an association with the nuclear matrix of the whole looped DNA fragment [Iarovaia et al, 2005]. In the same study it was observed that genes transcribed at a very low level were not necessarily associated with the nuclear matrix [Iarovaia et al, 2005].…”
supporting
confidence: 93%
See 3 more Smart Citations